Adipose Tissue Insulin Resistance is Closely Associated with Metabolic Syndrome in Northern Chinese Populations - Zhang K; Pan H; Wang L; Yang H; Zhu H; Gong F (Diabetes, Metabolic Syndrome and Obesity, 2021)
Kun Zhang,1,2 Hui Pan,1 Linjie Wang,1 Hongbo Yang,1 Huijuan Zhu,1 Fengying Gong1 1Key Laboratory of Endocrinology of National Health Commission, Department of Endocrinology, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Endocrinology, Shijiazhuang People’s Hospital, The People Affiliated Hospital of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of ChinaCorrespondence: Huijuan Zhu; Fengying GongKey Laboratory of Endocrinology of National Health Commission, Department of Endocrinology, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, 1# Shuai Fu Yuan Hu Tong, Dong Dan, Beijing, 100730, People’s Republic of ChinaTel +86-10-69155100Fax +86-10-69155073Email shengxin2004@163.com; fygong@sina.comObjective: Adipose tissue insulin resistance is a common feature of obesity-related metabolic diseases. However, the relationship between adipose tissue insulin resistance and metabolic syndrome (MS) has not been fully elucidated. Here, we explored the relationship between the adipose tissue insulin resistance index (Adipo-IR) (fasting insulin × free fatty acids) and MS and the predictive power of Adipo-IR for MS in northern Chinese populations.Methods: A total of 312 subjects, 186 subjects with MS, 80 nonmetabolic syndrome (NMS) subjects with central obesity, and 46 normal controls were recruited. The general clinical information, biochemical measurements, and oral glucose tolerance tests were evaluated. Serum adiponectin levels were determined using enzyme linked immunosorbent assay (ELISA).Results: Adipo-IR was 2.32-fold higher in NMS subjects and 2.62-fold higher in MS subjects than in normal controls in male subjects; in female subjects, it was 1.75-fold and 3.58-fold higher, respectively (P < 0.05). Female subjects with MS had higher Adipo-IR than male subjects (P < 0.001). Adipo-IR was independently positively correlated with waist circumference, triglyceride, aspartate aminotransferase, and fasting blood glucose and negatively correlated with adiponectin (P < 0.05). Subjects with the highest Adipo-IR tertile had a 2.758-fold higher risk of MS than subjects with the lowest tertile after adjusting for potential confounders (95% conﬁdence interval: 1.552– 9.096; P = 0.003). Receiver operating characteristic curve analysis showed that the predictive power of Adipo-IR for MS was 73.1% and 79.2% in male and female subjects, respectively, with optimal cutoff values of 3.84 and 5.92 mU/L×mmol/L.Conclusion: Adipo-IR provides a simple method to study adipose tissue insulin sensitivity. Adipo-IR is associated with MS and is an important predictor of MS.Keywords: adipose tissue insulin resistance, Adipo-IR, metabolic syndrome, obesity